SPEAKING CLASS EXERCISES USING THE SHADOWING PODCAST CONTENT TO WORK ON PRONUNCIATION - Suseno, Edy (Innovare Journal of Social Sciences, 2024)
English as a foreign language 1st-year students is introduced to speaking flaws. To remedy the pronunciation faults, 10 freshmen joined the treatment. To take part, they need access to gadgets with dependable internet. As a way to conduct the lesson outside of the classroom, the instructor set up a WhatsApp group. After finishing with the student member list, the teacher posted the podcast’s monologue’s content. He instructed the student to push the play button to hear the first sentence. Then, they paused and stated it once more. They went on until the delivery was finished. To perform shadowing, the student repeated the voice from the beginning. They all simultaneously spoke in response to the voice they heard. Continue doing this till the speech is over. After that, the transcript was spoken aloud for recording and forum posting. The lecturer then displayed the URL for the podcast’s talk. He repeated to them the same instructions; they had been given before. The students’ uploaded recording was entered into the transcription application to get the transcription. The teacher evaluated the transcription generated by a native speaker with the findings to find out how many pronunciation problems there were. All of the data were analyzed using a mixed-methods approach. The results showed that once the treatment started, the pupils’ pronunciation improved. Teachers can adapt this discovery to teach the related disciplines. It also inspires other researchers to conduct more research.